DO INVESTORS GET BENEFITS FROM CORPORATE GREEN SUKUK ISSUANCE - Riaz, Tabassum; Selamat, Aslam Izah; Nor, Normaziah Mohd; Hassan, Ahmad Fahmi Sheikh (Journal of Islamic Monetary Economics and Finance, 2024)
This study evaluates whether investors benefit from green sukuk by examining the responses of stock returns to the announcements of corporate green sukuk (green Islamic bonds) issuance. Applying the standard event study methodology, it finds that stock returns respond positively and significantly to the announcements of green sukuk issuance, suggesting that investors perceive and react favorably to the announcement. This significantly positive response is observed both for the individual firm (through CARs) and for a sample of all firms (through CAARs). Thus, it can be concluded that investors benefit from the announcements of green sukuk issuance. Further, this study draws a comparative analysis of investors’ response to the announcements of corporate green sukuk and corporate green bond issuance, and the findings also show that investors respond positively to the announcements of green bond issuances. However, the investors’ response is slightly higher to the announcements of corporate green sukuk issuance compared to corporate green bonds, and the investors get slightly more benefit from green sukuk issuance as compared to green bond issuance. These finding inform policymakers for the formulation of strategies to attract investors by integrating green bonds with shariah principles to fund environment-friendly projects and consequently mitigate the climate change risk. ACKNOWLEDGEMENT This research was funded by University of the Punjab, Lahore-Pakistan under the Overseas Ph.D. Scholarship for faculty members.